Physical mesomechanics of heterogeneous media and computer-aded design of materials - Panin V. E. Viktor Evgenyevich; Yigorushkin V. Yi.; Macarov P.V.; Nemirovich-Danchenko M. M. Mikhail Mikhailovich (Cambridge, Cambridge International Science Publishing Ltd., 1996)
В фонде НТБ ТПУ отсутствует